Analysis of the Effect of Company Financial Performance on Financial Distress at Pupuk Indonesia Subsidiaries - Putri Hardian, Qanita Marsha; Vendy, Vicky (Accounting Department, Faculty of Business and Management, Universitas Internasional Batam, 2023)
Purpose - This study uses the subsidiaries of PT. Pupuk Indonesia's Springate Score and Altman Z-Score to investigate the relationship between the financial performance of a business and its financial situation. Additionally, this study looks into whether the outcomes of the calculations for the Altman Z-Score and Springate Score differ significantly. Research Method - The technique of purposeful sampling was used to gather samples from the 2017–2021 annual reports of five PT. Pupuk Indonesia subsidiaries. Findings - The significant distinction comparing the two test results was further investigated in this study using the Mann-Whitney method. Implication - Based on the results of computations utilizing distinct financial ratios, the Altman Z-Score and Springate Score models show that liquidity issues can be forecast. However, there is a substantial discrepancy between the two models.